Uji Disolusi Beberapa Tablet Parasetamol yang Ada di Perdagangan - Maria Dona Octavia; Resita Sandra; Auzal Halim (Jurnal Farmasi Higea, 2009)
The dissolution test four generic tablets and one branded name of parasetamol tablets has been undertaken. Method applied was in the paddle method as required by Pharmacopea of Indonesian ed. IV. Paracetamol concentration measured spectrophotometrically at maximum wave length of 243 nm in dissolution medium pH 5.8 phosphate buffer solution. The result dissolution test to comply with tolerance is not less than 80% of the labeled amount of paracetamol is dissolved in tweenty minutes. The dissolution about drown from the plot between percentage of paracetamol dissolved versus time.The percentage of paracetamol dissolved at T30 analyzed by using ANOVA test. Result showed in the dissolution rates between generic 1,2,3,4 and branded name were significant different take. Then continued to DUNNET test , only generic 2 tablets was not significantly difference whereas the other generic tablets were significant differences.